2006
DOI: 10.1097/01.mib.0000200323.38139.c6
|View full text |Cite
|
Sign up to set email alerts
|

Specificities of the fecal microbiota in inflammatory bowel disease

Abstract: In IBD the dominant fecal microbiota comprises unusual bacterial species. Moreover, CD and UC fecal microbiota harbor specific discrepancies and differ from that of IC and healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
244
5
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(279 citation statements)
references
References 41 publications
19
244
5
11
Order By: Relevance
“…Both host and microbial factors influence bacterial opportunism and deficiencies in beneficial microbes may also contribute to chronic intestinal inflammation. Decreased counts of Faecalibacterium prausnitzii have been observed in fecal samples from IBD patients (19,20), and low counts of these bacteria appear to predict postsurgical recurrence (21). A decreased relative abundance of Bifidobacterium in the gut microbiota of IBD patients has also been observed (22).…”
mentioning
confidence: 84%
“…Both host and microbial factors influence bacterial opportunism and deficiencies in beneficial microbes may also contribute to chronic intestinal inflammation. Decreased counts of Faecalibacterium prausnitzii have been observed in fecal samples from IBD patients (19,20), and low counts of these bacteria appear to predict postsurgical recurrence (21). A decreased relative abundance of Bifidobacterium in the gut microbiota of IBD patients has also been observed (22).…”
mentioning
confidence: 84%
“…Future randomized, placebocontrolled large clinical trials are needed before we can implement prebiotics in our standard medical armamentarium for IBD. The number of adherent mucosal bacteria is increased in Crohn's disease patients 93 Inflammation and lesions generally occur in intestinal regions with the highest number of bacteria 3 Antibiotic treatment is a viable treatment option for some IBD patients 94 Luminal and mucosa-associated microflora of IBD patients differs from healthy controls 95,96 Diversion of the fecal stream induces clinical improvement in Crohn's patients 97 Inflamm Bowel Dis. Author manuscript; available in PMC 2016 December 09.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been shown that Crohn's patients have a defect in bacterial clearance [8] and polymorphisms in receptors that recognize bacteria are overrepresented in patients [3,4]. The microflora in the intestinal mucosa and fecal samples from Crohn's patients has also shown significant changes compared to controls, often with a predominance of potentially harmful bacteria or a decrease in beneficial bacteria [9,10]. Finally, studies in animal models show that bacteria are required to develop chronic intestinal inflammation and aberrant bacterial recognition can trigger the breakdown of intestinal tolerance [3][4][5].…”
Section: Overreactivity To Intestinal Bacteria Underlies Crohn's Diseasementioning
confidence: 99%